Patient pathways during acute in-hospital stroke treatment: a qualitative multi-method study - Busetto, Loraine; Hoffmann, Johanna; Stang, Christina; Amiri, Hemasse; Seker, Fatih; Purrucker, Jan; Ringleb, Peter A.; Nagel, Simon; Bendszus, Martin; Wick, Wolfgang; Gumbinger, Christoph (International journal of integrated care, 2022)
Introduction: Patients experiencing acute ischemic stroke should access treatment as soon as possible to increase their chances for survival without severe disability. Given the increased complexity of stroke treatment from the provider and patient perspective, this study provides an overview of the pathways followed by stroke patients during in-hospital treatment. - - Methods: This qualitative study combined twenty-seven observations and fifteen staff interviews at a German comprehensive stroke center providing endovascular treatment (“EVT hospital”). Analysis was based on the COMIC Model for the comprehensive evaluation of complex health care interventions and a grounded theory approach. - - Results: The patient pathways during in-hospital treatment span the phases (1) admission to hospital, (2) receiving recanalization therapies, and (3) in-patient treatment. Before admission to the EVT hospital, interactions between staff members from the EVT hospital and patients take place as part of the telestroke consultations during which the EVT hospital’s ED neurologist meets the patient via a video- and audio-based connection. During the second phase, when IVT and/or EVT are provided to the patient, three teams (ED, neuroradiology and ICU team) with direct patient interactions intersect at the angiography suite until mechanical recanalisation treatment ends and the patient is transferred to the SU or ICU. In the third phase, the patients are treated on the SU or ICU and staff members interact with them according to a pre-defined schedule as well as based on individual needs. - - Discussion: Our results show that most direct staff-patient interactions are focussed within one phase, with a smaller number of interactions extending to other phases, and no professional (group) with direct patient interactions cover more than two phases of the acute stroke pathway. Future research should investigate how the pathways described here are experienced from the patient perspective, including how the organisation of visible care processes may influence patient satisfaction. Findings can be translated to accessible patient information resources as well as input for digitalisation efforts, provider orientation and training.
Gesehen am 15.06.2022